Investigating dynamic amplification factor of railway masonry arch bridges through dynamic load tests. (20th September 2018) - Ataei, Shervan; Miri, Amin
Highlights: Dynamic load testing of 11 masonry arch bridges. Determining dynamic amplification factor of bridges based on displacement measurements. Studying the correlation of dynamic amplification factor with structural geometrical and mechanical characteristics. Comparing experimental dynamic amplification factor with proposed values of standards. Abstract: Structural assessment of masonry bridges is of great importance due to long service-life and deterioration of masonry and a growing demand for increasing the axle load. An important factor in doing so is the dynamic amplification factor (DAF), which accounts for dynamic impact of moving trains on a bridge. Accurate evaluation of DAF leads to sustainable management of existing bridges. A total of 845 dynamic load tests are carried out on 11 masonry arch bridges in Iranian railway network and results are used to assess the effect of train formation, train speed, span length, rise/span ratio, first natural frequencies in vertical and lateral directions, and combined modulus of elasticity of masonry and mortar on DAF. The correlation coefficients between first vertical frequency and modulus of elasticity and DAF are 0.53 and 0.56, respectively, which are the highest amongst studied parameters. Moreover, root mean square deviation between experimental DAF values and those determined according to various standards are determined and compared.